Chariocrinus -(Crinoidea: Articulata) from the Latady Formation, Behrendt and Hauberg Mountains, Ellsworth Land, Antarctica - Eagle, M.K.; Hikuroa, D. (Royal Society Of New Zealand, 2003)
Specimens of a late Bajocian to early Callovian isocrinid assigned to Pentacrinites cf. P. californicus (Clark), and specimens collected by Hikuroa in 1999-2000, are described as a new species of Chariocrinus. All specimens were collected from rock exposures of the Latady Formation at eight localities in the Behrendt and Hauberg Mountains, Ellsworth Land, Antarctica. The fauna, preserved in situ at all localities, is essentially complete, but due to tectonism, localities may have been moved many kilometres from their original position. Chariocrinus latadiensis n. sp. is compared with congeneric species and those of Hispidocrinus. It is the first record of the genus in the Southern Hemisphere, which has European Tethyan affinities. Columnals are pentastellate to pentalobate, and the symplectial articula appear diagnostic of Hispidocrinus but are included in Chariocrinus on the basis of spineless axillaries and fused adjacent crenulae; those of Hispidocrinus are spined and separated by a furrow or smooth band, respectively. A single pluricolumnal (?Apiocrinus) is the only associated crinoid found at any of the localities. Chariocrinus latadiensis lived a semi-sessile existence on a volcarenite substrate in association with vagrant ammonites, epifaunal and infaunal bivalves, and epifaunal brachiopods. The benthic taxa lived in shallow, low energy marine environments in the Middle Jurassic, part of a submarine back-arc basin near the shore off southeastern Gondwana. An open access copy of this article is available from the publishers website.